Corporate Social Responsibility and Horizontal Differentiation in Imperfect Competitive Markets with Global Warming Effects - Barboza, Gustavo; Trejos, Sandra (Journal of Reviews on Global Economics, 2013)
Abstract: This study develops a model of corporate social responsibility (CSR) behavior that is compatible with both the mutual goals of profit maximization and the reduction of global warming effects. The theory developed in this paper indicates that, under perfect competitive and unregulated markets, firms must take an innovative entrepreneurship approach to reduce global warming externalities, and, consequently, respond to the demands of stakeholders to behave in a CSR fashion. In this setting, managers and firms find incentives to pursue strategies leading to horizontal differentiation when a segment of the market has strong revealed consumption preferences for environmentally friendly products, and when consumers derive a consumption disutility from products creating global warming effects. To achieve these goals, firms using a safe technology also incur certification/labeling costs in order to gain market power. That is, this study demonstrates that, in unregulated competitive markets, efforts to clearly identify sources of global warming effects require innovative entrepreneurship thinking above and beyond government regulatory efforts. Thus, firms behaving in a CSR fashion may achieve monopolistic power, and therefore positive profits. In sum, our model demonstrates that CSR is compatible with the triple bottom line of economic, social and environmental performance.